A characterization of convex hypersurfaces in Hadamard manifolds - Erdogan, Mehmet; Yilmaz, Gülsen (MATHEMATICA SCANDINAVICA, 2005)
The aim of this paper is to give a characterization of strictly convex hypersurfaces in a Hadamard manifold.